An Unusual First‐Trimester Ultrasound Presentation of the Acrania‐Anencephaly Sequence: The "Turkish Turban" Sign. (9th November 2019) - Sepulveda, Waldo; De La Maza, Francisco; Meagher, Simon
Abstract : A previously unrecognized first‐trimester presentation of the acrania‐anencephaly sequence is described. Ultrasound features included a constriction ring around the external base of the developing skull and an enlarged globular head, resembling a Turkish turban, with large cystic spaces replacing the brain. This constellation of findings was noted in 3 first‐trimester fetuses. In 2 of them, it was possible to identify the amniotic membrane attached to the constriction ring. One case presented with anencephaly and fetal demise at 16 weeks. The other 2 women terminated the pregnancies and aborted anencephalic fetuses. This subtype of the acrania‐anencephaly sequence could represent an earlier segmental rupture of the amnion, which subsequently entraps the developing fetal skull.